Preclinical Evidence of Berberine on Non-Alcoholic Fatty Liver Disease: A Systematic Review and Meta-Analysis of Animal Studies - Ren, Sichen; Ma, Xiao; Wang, Ruilin; Liu, Honghong; Wei, Ying; Wei, Shizhang; Jing, Manyi; Zhao, Yanling (Frontiers in Pharmacology, 2021)
As the life style and diet structure translate, non-alcoholic fatty liver disease (NAFLD) is prevalent all over the world. Some phytomedicines containing berberine (BBR) have been extensively used for centuries as a part of Ayurvedic and traditional Chinese medicine. The goal of this systematic review is to investigate the preclinical evidence of BBR on NAFLD models. These following relevant databases including Web of Science, PubMed, the Cochrane Library and Embase were retrieved from inception to May 2021. The content involved BBR on different animal models for the treatment of NAFLD. The Systematic Review Center for Laboratory animal Experimentation (SYRCLE) Animal Experiment Bias Risk Assessment Tool was used to for assess the methodological quality and RevMan 5.4 software was used to conducted the meta-analysis based on the Cochrane tool. A total of 31 studies involving 566 animals were included, of which 5 models and 5 animal breeds were reported. The results showed that TC, TG, ALT, AST, HDL-C, LDL-C, FBG, FINS and FFA in the group treated with BBR were significantly restored compared with those in the model group. HOMA-IR had a significant downward trend, but the result was not significantly different (P = 0.08). The subgroup analysis of the different models and different animal breed indicated that BBR could ameliorate the aforementioned indicator levels, although some results showed no significant difference. Finally, we summarized the molecular mechanisms by which berberine regulated NAFLD/NASH, mainly focusing on activating the AMPK pathway, improving insulin sensitivity and glucose metabolism, regulating mitochondrial function, reducing inflammation and oxidative stress, regulating cell death and ER stress, reducing DNA methylation，as well as regulating intestinal microenvironment and neurotoxicity. The preclinical evidence suggested that BBR might be an effective and promising drug for the treatment of NAFLD/NASH. In addition, further studies with more well-designed researches are needed to confirm this conclusion.